Assessing undergraduate students' level of independent learning as a manifestation of learner autonomy - Rochma, Anis Firdatul (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
Previous studies related to learner autonomy have been conducted, yet those studies seem to focus on formative assessment as a guarantee for the development of learner autonomy. This study is projected to assess the undergraduate students' level of independent learning since learner autonomy tends to manifest itself in various degree of independence. A questionnaire related to independent learner was adopted as the main instrument. The data were analyzed both quantitatively and qualitatively. The quantitative data were obtained to assess the students' level of independent learning while the qualitative data were gained to reveal the students' perceptions and thoughts about independent learning. The results show that most of the students have moderate independence. Moreover, most of the students are considered able to relate the concept of independent learning with various degrees of independence that are included in the notion of learner autonomy. Nevertheless, the findings also show that some students tend to have low interest in their studies, low expectation about what they want to learn, and low possibility in questioning what they are told. It is important for the teachers to enhance the students' moderate independence into high independence by providing the access to a number of learning opportunities. Thus, the students are able to critically reflect on their own learning and effectively develop awareness to help them learn constructively.